Digitizing Learning Media of Advertising Communication Based on Multimedia Animation at Politeknik Negeri Media Kreatif - Zaenab Zaenab; Hawa Asma Ul Husna (STMIK Budi Darma, 2021)
Learning Media has a very important role in the lecture process. Currently, the State Polytechnic of Creative Media (Polymedia) is not maximal in Digitizing Learning Media, lecturers still use the lecture method in explaining Advertising Communication material, Polymedia should have multimedia and animate interesting lectures for students. The State Polytechnic of Creative Media, Jakarta campus, is the object of research. The specific objective of this research is the digitization of Learning Media in the Multimedia Animation-Based Advertising Communication course. The urgency of the research is the importance of computer-based multimedia in learning so that real efforts need to be made in order to improve the quality of learning so that learning objectives can be effectively achieved. This study uses the Multimedia Development Life Cycle (MDLC) method with six stages, namely: Design, Material Collecting, Assembly, Testing, and Distribution